Community Service through Family Counseling as an Effort to Prevent Siri Marriage - Yeni, Putri; Husniah, Hafizatul (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
This dedication is motivated by the many problems that arise due to the occurrence of unregisteredmarriages. It is necessary to carry out community service through family counseling with the aim of forminga strong family in dealing with polemics and problems caused by unregistered marriages. So that theresilience of the participants in the household emerges. This family counseling activity is carried out throughseveral meetings according to the topics that have emerged during counseling. The implementationtechnique is in the form of discussion, FGD, and Family Counseling. The results of this activity are familycounseling participants. The important role of family counseling is to help families in dealing with problemsthat occur, as well as find the right solution, bring out the best potential, and develop the ability to worktogether as a family is facing difficulties.